2018
DOI: 10.4155/bio-2017-0196
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Technologies for Biotherapeutic Bioanalysis from a High-Throughput and Multiplexing Perspective: Insights from an AAPS Emerging Technology Action Program Committee

Abstract: This manuscript aims to provide insights and updates on emerging technologies from a throughput and multiplexing perspective and to update readers on changes in previously reported technologies. The technologies discussed range from nascent (ultrasensitive Cira, Intellicyt, Dynaxi and Captsure™) to the more established (Ella and SQIDlite™). For the nascent technologies, there was an emphasis on user interviews and reviews, where available, to help provide an unbiased view to our readers. For the Ella, a review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Despite the challenge of selecting visits/samples from a prospectively assessed cohort in which patients were not followed in lockstep nor flare rates predicted to have an equal number of preflare and pre-nonflare visits, we confirmed that immune changes occurred prior to clinical disease flare, whether assessed en masse or on an individual patient level, and this information was harnessed to inform a refined FRI. The microfluidic, automated Ella immunoassay platform, designed for commercial use with minimal batch effects between users, sites, and lots (11,(22)(23)(24), allowed for design of the refined FRI-11 for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the challenge of selecting visits/samples from a prospectively assessed cohort in which patients were not followed in lockstep nor flare rates predicted to have an equal number of preflare and pre-nonflare visits, we confirmed that immune changes occurred prior to clinical disease flare, whether assessed en masse or on an individual patient level, and this information was harnessed to inform a refined FRI. The microfluidic, automated Ella immunoassay platform, designed for commercial use with minimal batch effects between users, sites, and lots (11,(22)(23)(24), allowed for design of the refined FRI-11 for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of the available Ella™ assays is in the lower pg/mL range with a required sample volume between 2.5 and 50 µL. 16,17 While a vast literature is available on the use of SiMoA™ for the detection of plasma NfL levels, the assay based on Ella™ has been introduced more recently and its performance in comparison with the one observed on SiMoA™ needs to be understood. In a rst study, Ella™ and SiMoA™ were used to detect blood levels of NfL in serum samples of patients with multiple sclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…12− 15 Ella™ is a micro uidic cartridge-based immunoassay platform from ProteinSimple (part of Bio-Techne), which is widely used to quantify soluble biomarkers. 16,17 Different cartridge formats allow measuring 72 samples in one assay. Measures are performed in triplicates in three glass nanoreactors (GNRs) for each sample using a uorescent substrate, which helps to achieve a wide dynamic measuring range.…”
Section: Introductionmentioning
confidence: 99%
“…Array-based immunoassays were first described by Ekins et al and have been actively researched over the last 30 years. , In these immunoassays, capture antibodies are printed onto a planar surface and bind the target molecules in a sample that are subsequently labeled and detected. This type of immunoassay is amenable to multiplex protein detection by immobilizing capture antibodies specific to different proteins at predefined locations on a planar surface.…”
Section: Introductionmentioning
confidence: 99%